Pharmacological Activating Transcription Factor 6 Activation Is Beneficial for Liver Retrieval With ex vivo Normothermic Mechanical Perfusion From Cardiac Dead Donor Rats - Cheng, Nuo; Shi, Ji-Hua; Jin, Yang; Shi, Yuan-Bin; Liu, Xu-Dong; Zhang, Hua-Peng; Cao, Sheng-Li; Yang, Han; Guo, Wen-Zhi; Zhang, Shui-Jun (Frontiers in Surgery, 2021)
Background Normothermic machine perfusion (NMP) could be beneficial for organ retrieval from donors after cardiac death (DCD). Activating transcription factor 6 (ATF6) was recently shown to mitigate liver ischemia/reperfusion injury and confer protection. The aims of this study were to assess the implication of ATF6 in liver retrieval from DCD rat livers with NMP and explore the effect of pharmacologic ATF-6 activation on liver retrieval. Methods The livers from DCD rats were exposed to 30 min of warm ischemia and 8 h cold preservation followed by 2 h NMP with or without an ATF6 activator in the perfusate. Perfusates and livers were harvested to detect ATF6 expression, liver function, and inflammation. Results DCD livers with NMP were associated with ATF6 overexpression and activation based on IHC and WB (P<0.05). The ATF6 activator downregulated perfusate aminotransferases, decreased the Suzuki score, downregulated CD68 and MPO based on IHC, reduced TNFα and IL-6 levels based on RT-qPCR and ELISA, decreased MDA levels, and increased SOD activity in the perfused livers (P<0.05). Conclusion ATF6 is important for liver retrieval, and an exogenous ATF6 activator accelerates liver retrieval from DCD rats in an ex vivo NMP model.